Educación física y el libro de texto: Entre la brecha y el despertar - de Souza Júnior, Marcílio Barbosa Mendonça; do Amaral, Lucas Vieira; de Melo, Marcelo Soares Tavares; Darido, Suraya Cristina [UNESP]; Lima, Ricardo Bezerra Torres (My University, 2015)
The textbook also receiving some criticism, hold the potential to contribute to the qualification of the teaching and learning of the various curriculum components. However, it is common to notice that Physical Education has shown that remote resource type material, with some isolated initiatives of using this. In this context, this study aimed to recognize, in the literature, what factors contributed to the formation of the gap between physical education and textbooks and elaborations have been made recently in this field on such a book. We conclude that the historical legacy of Physical Education is one of the main driving factors of this hiatus, but recently began to be minimized by design initiatives and use of the textbook in the field.
Educaçao física e livro didático: Entre o hiato e o despertar
Physical education and textbook: Between gap and awakening
Keywords: Learning; Teaching materials; Textbooks